Isolation of Heavy Metal Resistant Bacteria for Sustainable Crop Production - Nath, Soumitra; Sharma, Indu; Deb, Bibhas; Singh, Virender (International Journal of Bio-resource and Stress Management, 2023)
Thirty five heavy metal resistant bacteria were isolated from contaminated crop field of Southern Assam, India, against copper, zinc, cadmium and lead. The predominant isolates were identified as Proteus sp., Klebsiella sp., Staphylococcus sp., Bacillus sp. and Pseudomonas sp.. Some isolates exhibited high resistance to heavy metals with minimum inhibitory concentration (MIC) for heavy metals as 60 μg ml-1 (for copper), 180 μg ml-1 (for lead) 130 μg ml-1 (for cadmium) and 1800 μg ml-1 (for zinc). They also showed multiple heavy metal tolerance and were multi-antibiotic resistant. There was decrease in total count and microbial population diversity with increasing metal concentrations. The present study showed a correlation between heavy metal resistance and antibiotic tolerance among bacterial isolates. The effect of heavy metal resistant strains on Oryza sativa inoculated in contaminated soil showed a remarkable increase in the shoot length when compared with control pots.